Blockchain Implementation for Digital Financial Transaction Data Security - Achmady, Sayed (Westscience Press, 2025)
The rapid expansion of digital financial services in Indonesia has increased the importance of ensuring secure, transparent, and reliable transaction data management. Traditional centralized financial systems face challenges related to data breaches, fraud, and system vulnerability, prompting the need for more advanced security technologies. This study examines the implementation of blockchain technology in enhancing the security of digital financial transaction data in Indonesia. A quantitative research approach was employed using a sample of 65 respondents who are users and practitioners of digital financial services. Data were collected through a structured questionnaire measured on a five-point Likert scale and analyzed using SPSS version 25. The results of simple linear regression analysis indicate that blockchain implementation has a positive and significant effect on digital financial transaction data security. Blockchain implementation explains 54.9% of the variance in data security, highlighting its substantial role in improving confidentiality, data integrity, transparency, and fraud prevention. The findings provide empirical support for the adoption of blockchain technology as a strategic solution to strengthen digital financial system security in Indonesia.